The Impact of Advertising and Sales Performance in Mukwano Industry Kampala Branch. - Atamba, Peter (Kabale University, 2023)
The study aimed at assessing the effect of advertising on sales performance of an organization, a case study being Mukwano industry in kampala. The study was mainly looking at advertising and sales of Mukwano industry and this was effective to the organisation. The researcher used cross sectional research design with both qualitative and quantitative methods with a population of 150 people out of which a sample of 50 employees were chosen. Stratified sampling design was used to divide the employees into strata which were departments under which employees worked, and they included Marketing, Operational, Production and supply departments. Using simple random sampling respondents were chosen from the different departments selected and questionnaires distributed to the selected respondents from the four departments in the industry. Both the primary and secondary data was collected during the collection of data. Data was collected by use of questionnaires and observation method and analyzed in form of tables. Findings revealed that Mukwano advertises most of its products and it uese different forms of advertising and media, but the level of Mukwano' s sales was declining despite of their frequent advertisements. There was a strong relationship between advertising and sales performance. The industry should use most of the local languages commonly used in Uganda to win customers from all tribes, use of e marketing to be adopted by the industry to reach most of the people who can access the internet than listen to radios and televisions, and also the use of celebrities in advertising their products, and finally the researcher recommends the use of other forms of advertising for example sponsoring events and also the use of mobile phones to advertise.